Tinjauan Yuridis Tindak Pidana Penganiayaan Yang Mengakibatkan Luka Berat Studi Putusan Nomor 127/Pid.B/2022/Pn.Mrs - Andi Rahmah; Andi Zulkarnain; Idznih shadria (Pledoi Law Jurnal, 2024)
This research aims to determine the application of material criminal law to perpetrators of criminal acts of abuse which resulted in serious injuries in case